A water-absorbing ceramic material, preparation method and application thereof
By using raw materials such as dolomite, diatom mud, modified nano zinc oxide agent and filler modifier, ceramic materials with excellent water absorption and antibacterial properties are prepared, which solves the problem of difficult coordination between water absorption and antibacterial properties of ceramic materials, and improves their wear resistance and achieves higher application efficiency.
Patent Information
- Application Number
- CN202411901483.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-23
AI Technical Summary
Existing ceramic materials are difficult to achieve a coordinated balance between water absorption and antibacterial properties, and at the same time, their wear resistance is poor, which limits their application efficiency.
The ceramic materials with excellent water absorption and antibacterial properties are prepared by ball milling and sintering processes using raw materials such as dolomite, diatom mud, modified nano zinc oxide agent and filler modifier. The modified nano zinc oxide agent enhances the antibacterial properties of ceramic materials through the combination of nano zinc oxide and the modified liquid, while the Maifanshi-lanthanide and filler modifier optimizes water absorption and wear resistance.
The coordinated balance between water absorption and antibacterial properties of ceramic materials is achieved, and its wear resistance is significantly improved, making it more efficient in a variety of application scenarios.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramics, and in particular to a water-absorbing ceramic material, a preparation method and application thereof. Background Art
[0002] Ceramics is a general term for pottery and porcelain. Common ceramic materials include clay, alumina, kaolin, etc. Ceramic materials are generally hard but less plastic. In addition to being used in tableware and decoration, ceramics also play an important role in the development of science and technology. Existing ceramic materials are used in coasters, tea trays, photo frames, hooks, refrigerator magnets, heat insulation pads, and porcelain plate paintings. They have poor water absorption performance. In order to improve the water absorption performance, bacteria are easily bred, which in turn affects the antibacterial properties of ceramic materials. It is difficult for ceramic materials to achieve a coordinated balance between water absorption and antibacterial properties. In addition, ceramic materials have poor wear resistance, which limits the efficiency of ceramic materials. Summary of the invention
[0003] In view of the defects of the prior art, the purpose of the present invention is to provide a water-absorbing ceramic material, a preparation method and application thereof, so as to solve the problems raised in the above background technology.
[0004] The present invention solves the technical problem by adopting the following technical solution:
[0005] The present invention provides a water-absorbing ceramic material, comprising the following raw materials in parts by weight:
[0006] 35-40 parts of dolomite, 15-20 parts of diatom mud, 6-8 parts of modified nano zinc oxide agent, 2-5 parts of clay, 4-7 parts of filler modifier, and 20-25 parts of water.
[0007] Preferably, the preparation method of the modified nano zinc oxide agent is:
[0008] S01: First, prepare a 5% by weight dopamine Tris solution and a 4% by weight aluminum nitrate solution; then, add 1-3 parts by weight of silane coupling agent KH550 and 2-4 parts by weight of hollow glass microspheres to 2-5 parts by weight of the dopamine Tris solution, and then add 1-2 parts by weight of the aluminum nitrate solution, stir thoroughly, and obtain a modified solution;
[0009] S02: Stirring and modifying the nano zinc oxide in a modification liquid 3-5 times the total weight of the nano zinc oxide, and completing the stirring to obtain a nano zinc oxide liquid;
[0010] S03: 3-5 parts of medical stone, 2-4 parts of lanthanum oxide, 4-7 parts of sodium alginate solution and 2-4 parts of sodium silicate powder are mixed uniformly by weight, then filtered and dried, and heat treated at 210-230° C. for 1 hour. After the treatment is completed, air-cooled to room temperature to obtain medical stone-lanthanide;
[0011] S04: The medical stone-lanthanide and nano zinc oxide solution are mixed in a mass ratio of 2:3, and the mixture is ball-milled at a speed of 1000 r / min for 1 h. After the ball-milling is completed, the mixture is filtered and dried to obtain a modified nano zinc oxide agent.
[0012] Preferably, the stirring speed of the stirring modification treatment is 350-400 r / min, and the stirring is for 10 min.
[0013] Preferably, the mass fraction of the sodium alginate solution is 4-6%.
[0014] Preferably, the preparation method of the filler modifier is:
[0015] S11: first prepare a yttrium nitrate solution with a mass fraction of 4-6% and a phosphate buffer solution with a pH value of 6.0; then evenly mix the nano-titanium dioxide, the yttrium nitrate solution and the phosphate buffer solution in a weight ratio of 2:5:1 to obtain a nano-titanium dioxide agent;
[0016] S12: ultrasonically treat the flaky chromium oxide agent and the nano titanium dioxide agent in a weight ratio of 2:5. After the ultrasonic treatment is finished, filter and dry to obtain a filler modifier.
[0017] Preferably, the ultrasonic power of the ultrasonic treatment is 350-400W, and the ultrasonic time is 20-30min.
[0018] Preferably, the preparation method of the flaky chromium oxide agent is:
[0019] Add 3-5 parts of nano calcium carbonate, 1-2 parts of vermiculite and 1-2 parts of carboxymethyl cellulose by weight to 5-8 parts of sodium lignin sulfonate solution, stir well, and obtain a ball mill;
[0020] The flaky chromium oxide and the ball milling agent were mixed in a weight ratio of 5:3 and ball milled at a ball milling speed of 1500 r / min for 1 hour. After the ball milling was completed, the mixture was filtered and dried to obtain the flaky chromium oxide agent.
[0021] Preferably, the mass fraction of the sodium lignin sulfonate solution is 2-5%.
[0022] The present invention also provides a method for preparing a water-absorbing ceramic material, comprising the following steps:
[0023] Dolomite, diatom mud, modified nano zinc oxide agent, clay, filler modifier and water are stirred and mixed, ball milled in a ball mill for 2 hours at a ball mill speed of 1000r / min, put into a mold for forming, and finally sintered to obtain a water-absorbing ceramic material.
[0024] Preferably, the sintering temperature is 1210-1230° C., and the sintering time is 5 hours.
[0025] The present invention also provides an application of the water-absorbing ceramic material, wherein the water-absorbing ceramic material is applied to coasters, tea trays, photo frames, hooks, refrigerator magnets, heat-insulating pads or porcelain plate paintings.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] The water-absorbing ceramic material of the present invention uses dolomite, diatom mud and clay as raw materials, and by adding modified nano zinc oxide agent and filler modifier, the obtained water-absorbing ceramic material has excellent water absorption and antibacterial coordinated balance improvement, and the water-absorbing ceramic material has significant wear resistance performance;
[0028] The modified nano zinc oxide agent uses nano zinc oxide as a matrix material to enhance the antibacterial property of the water-absorbing ceramic material. At the same time, after being improved by a modified liquid, the hollow glass microspheres in the modification are blended with a silane coupling agent KH550, a dopamine Tris solution and an aluminum nitrate solution, and the hollow glass microspheres provide a spherical interface, thereby playing a bearing effect, optimizing the distribution of nano zinc oxide, thereby improving the antibacterial property of the water-absorbing ceramic material, and after blending and coordinating the modified liquid raw materials, the performance effect of the water-absorbing ceramic material is enhanced, and the medical stone-lanthanide body uses medical stone as a matrix to enhance the porosity of the system and optimize the water absorption of the water-absorbing ceramic material, and then blends lanthanum oxide, sodium alginate solution and sodium silicate powder evenly, and then heats and improves, so that the medical stone-lanthanide body can better cooperate with the nano zinc oxide liquid, so that the modified nano zinc oxide agent can better improve the antibacterial property and water absorption of the water-absorbing ceramic material, and synergistically improve the performance effect of the water-absorbing ceramic material;
[0029] The filler modifier is prepared by mixing nano titanium dioxide, yttrium nitrate solution and phosphate buffer solution to obtain a nano titanium dioxide agent. Nano titanium dioxide is used as a matrix and then matched with a flaky chromium oxide agent. The flaky chromium oxide in the flaky chromium oxide agent and a ball mill are evenly ball-milled. Then, nano calcium carbonate, vermiculite, carboxymethyl fiber and sodium lignin sulfonate solution are fully stirred to obtain a ball mill. The raw materials in the ball mill are mutually harmonized to achieve synergistic effects, so that the filler modifier obtained can better coordinate with the modified nano zinc oxide agent, and the performance stability of the water-absorbing ceramic material as well as the water absorption and antibacterial coordination are further improved. DETAILED DESCRIPTION
[0030] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] A water-absorbing ceramic material of this embodiment includes the following raw materials in parts by weight:
[0032] 35-40 parts of dolomite, 15-20 parts of diatom mud, 6-8 parts of modified nano zinc oxide agent, 2-5 parts of clay, 4-7 parts of filler modifier, and 20-25 parts of water.
[0033] The preparation method of the modified nano zinc oxide agent of this embodiment is:
[0034] S01: First, prepare a 5% by weight dopamine Tris solution and a 4% by weight aluminum nitrate solution; then, add 1-3 parts by weight of silane coupling agent KH550 and 2-4 parts by weight of hollow glass microspheres to 2-5 parts by weight of the dopamine Tris solution, and then add 1-2 parts by weight of the aluminum nitrate solution, stir thoroughly, and obtain a modified solution;
[0035] S02: Stirring and modifying the nano zinc oxide in a modification liquid 3-5 times the total weight of the nano zinc oxide, and completing the stirring to obtain a nano zinc oxide liquid;
[0036] S03: 3-5 parts of medical stone, 2-4 parts of lanthanum oxide, 4-7 parts of sodium alginate solution and 2-4 parts of sodium silicate powder are mixed uniformly by weight, then filtered and dried, and heat treated at 210-230° C. for 1 hour. After the treatment is completed, air-cooled to room temperature to obtain medical stone-lanthanide;
[0037] S04: The medical stone-lanthanide and nano zinc oxide solution are mixed in a mass ratio of 2:3, and the mixture is ball-milled at a speed of 1000 r / min for 1 h. After the ball-milling is completed, the mixture is filtered and dried to obtain a modified nano zinc oxide agent.
[0038] The stirring speed of the stirring modification treatment in this embodiment is 350-400 r / min, and the stirring is 10 minutes.
[0039] The mass fraction of the sodium alginate solution in this embodiment is 4-6%.
[0040] The preparation method of the filler modifier of this embodiment is:
[0041] S11: first prepare a yttrium nitrate solution with a mass fraction of 4-6% and a phosphate buffer solution with a pH value of 6.0; then evenly mix the nano-titanium dioxide, the yttrium nitrate solution and the phosphate buffer solution in a weight ratio of 2:5:1 to obtain a nano-titanium dioxide agent;
[0042] S12: ultrasonically treat the flaky chromium oxide agent and the nano titanium dioxide agent in a weight ratio of 2:5. After the ultrasonic treatment is finished, filter and dry to obtain a filler modifier.
[0043] The ultrasonic power of the ultrasonic treatment in this embodiment is 350-400W, and the ultrasonic time is 20-30min.
[0044] The preparation method of the flaky chromium oxide agent of this embodiment is:
[0045] Add 3-5 parts of nano calcium carbonate, 1-2 parts of vermiculite and 1-2 parts of carboxymethyl cellulose by weight to 5-8 parts of sodium lignin sulfonate solution, stir well, and obtain a ball mill;
[0046] The flaky chromium oxide and the ball milling agent were mixed in a weight ratio of 5:3 and ball milled at a ball milling speed of 1500 r / min for 1 hour. After the ball milling was completed, the mixture was filtered and dried to obtain the flaky chromium oxide agent.
[0047] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 2-5%.
[0048] A method for preparing a water-absorbing ceramic material in this embodiment comprises the following steps:
[0049] Dolomite, diatom mud, modified nano zinc oxide agent, clay, filler modifier and water are stirred and mixed, ball milled in a ball mill for 2 hours at a ball mill speed of 1000r / min, put into a mold for forming, and finally sintered to obtain a water-absorbing ceramic material.
[0050] The sintering temperature of this embodiment is 1210-1230° C., and the sintering time is 5 hours.
[0051] The present embodiment provides an application of a water-absorbing ceramic material, wherein the water-absorbing ceramic material is applied to coasters, tea trays, photo frames, hooks, refrigerator magnets, heat-insulating pads, ceramic paintings, and the like.
[0052] Example 1: A water-absorbing ceramic material comprising the following raw materials in parts by weight:
[0053] 35 parts of dolomite, 15 parts of diatom mud, 6 parts of modified nano zinc oxide agent, 2 parts of clay, 4 parts of filler modifier, and 20 parts of water.
[0054] The preparation method of the modified nano zinc oxide agent of this embodiment is:
[0055] S01: First, prepare a 5% by weight dopamine Tris solution and a 4% by weight aluminum nitrate solution; then, add 1 part of silane coupling agent KH550 and 2 parts of hollow glass microspheres to 2 parts of dopamine Tris solution, and then add 1 part of aluminum nitrate solution, stir well, and obtain a modified solution;
[0056] S02: Stirring and modifying the nano zinc oxide in a modification liquid 3 times the total weight of the nano zinc oxide, and completing the stirring to obtain a nano zinc oxide liquid;
[0057] S03: 3 parts of medical stone, 2 parts of lanthanum oxide, 4 parts of sodium alginate solution and 2 parts of sodium silicate powder are mixed uniformly by weight, then filtered and dried, and heat treated at 210° C. for 1 h. After the treatment is completed, air-cooled to room temperature to obtain medical stone-lanthanide;
[0058] S04: The medical stone-lanthanide and nano zinc oxide solution are mixed in a mass ratio of 2:3, and the mixture is ball-milled at a speed of 1000 r / min for 1 h. After the ball-milling is completed, the mixture is filtered and dried to obtain a modified nano zinc oxide agent.
[0059] The stirring speed of the stirring modification treatment in this embodiment is 350 r / min, and the stirring is for 10 minutes.
[0060] The mass fraction of the sodium alginate solution in this embodiment is 4%.
[0061] The preparation method of the filler modifier of this embodiment is:
[0062] S11: first prepare a 4% by mass yttrium nitrate solution and a phosphate buffer solution with a pH value of 6.0; then evenly mix the nano titanium dioxide, the yttrium nitrate solution and the phosphate buffer solution in a weight ratio of 2:5:1 to obtain a nano titanium dioxide agent;
[0063] S12: ultrasonically treat the flaky chromium oxide agent and the nano titanium dioxide agent in a weight ratio of 2:5. After the ultrasonic treatment is finished, filter and dry to obtain a filler modifier.
[0064] The ultrasonic power of the ultrasonic treatment in this embodiment is 350W, and the ultrasonic time is 20min.
[0065] The preparation method of the flaky chromium oxide agent of this embodiment is:
[0066] Add 3 parts of nano calcium carbonate, 1 part of vermiculite and 1 part of carboxymethyl cellulose by weight into 5 parts of sodium lignin sulfonate solution, stir well, and obtain a ball mill;
[0067] The flaky chromium oxide and the ball milling agent were mixed in a weight ratio of 5:3 and ball milled at a ball milling speed of 1500 r / min for 1 hour. After the ball milling was completed, the mixture was filtered and dried to obtain the flaky chromium oxide agent.
[0068] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 2%.
[0069] A method for preparing a water-absorbing ceramic material in this embodiment comprises the following steps:
[0070] Dolomite, diatom mud, modified nano zinc oxide agent, clay, filler modifier and water are stirred and mixed, ball milled in a ball mill for 2 hours at a ball mill speed of 1000r / min, put into a mold for forming, and finally sintered to obtain a water-absorbing ceramic material.
[0071] The sintering temperature of this embodiment is 1210° C. and the sintering time is 5 hours.
[0072] The present embodiment provides an application of a water-absorbing ceramic material, wherein the water-absorbing ceramic material is applied to coasters, tea trays, photo frames, hooks, refrigerator magnets, heat-insulating pads, ceramic paintings, and the like.
[0073] Example 2: A water-absorbing ceramic material comprising the following raw materials in parts by weight:
[0074] 40 parts of dolomite, 20 parts of diatom mud, 8 parts of modified nano zinc oxide agent, 5 parts of clay, 7 parts of filler modifier, and 25 parts of water.
[0075] The preparation method of the modified nano zinc oxide agent of this embodiment is:
[0076] S01: First, prepare a 5% by weight dopamine Tris solution and a 4% by weight aluminum nitrate solution; then, add 3 parts by weight of silane coupling agent KH550 and 4 parts by weight of hollow glass microspheres to 5 parts by weight of the dopamine Tris solution, and then add 2 parts by weight of the aluminum nitrate solution, stir thoroughly, and obtain a modified solution;
[0077] S02: Stirring and modifying the nano zinc oxide in a modification liquid that is 5 times the total weight of the nano zinc oxide, and completing the stirring to obtain a nano zinc oxide liquid;
[0078] S03: 5 parts of medical stone, 4 parts of lanthanum oxide, 7 parts of sodium alginate solution and 4 parts of sodium silicate powder are mixed uniformly by weight, then filtered and dried, and heat treated at 230° C. for 1 h. After the treatment is completed, air-cooled to room temperature to obtain medical stone-lanthanide;
[0079] S04: The medical stone-lanthanide and nano zinc oxide solution are mixed in a mass ratio of 2:3, and the mixture is ball-milled at a speed of 1000 r / min for 1 h. After the ball-milling is completed, the mixture is filtered and dried to obtain a modified nano zinc oxide agent.
[0080] The stirring speed of the stirring modification treatment in this embodiment is 400 r / min, and the stirring is for 10 minutes.
[0081] The mass fraction of the sodium alginate solution in this embodiment is 6%.
[0082] The preparation method of the filler modifier of this embodiment is:
[0083] S11: first prepare a 6% by mass yttrium nitrate solution and a phosphate buffer solution with a pH value of 6.0; then evenly mix the nano titanium dioxide, the yttrium nitrate solution and the phosphate buffer solution in a weight ratio of 2:5:1 to obtain a nano titanium dioxide agent;
[0084] S12: ultrasonically treat the flaky chromium oxide agent and the nano titanium dioxide agent in a weight ratio of 2:5. After the ultrasonic treatment is finished, filter and dry to obtain a filler modifier.
[0085] The ultrasonic power of the ultrasonic treatment in this embodiment is 400 W, and the ultrasonic time is 30 min.
[0086] The preparation method of the flaky chromium oxide agent of this embodiment is:
[0087] Add 5 parts of nano calcium carbonate, 2 parts of vermiculite and 2 parts of carboxymethyl cellulose by weight into 8 parts of sodium lignin sulfonate solution, stir well, and obtain a ball mill;
[0088] The flaky chromium oxide and the ball milling agent were mixed in a weight ratio of 5:3 and ball milled at a ball milling speed of 1500 r / min for 1 hour. After the ball milling was completed, the mixture was filtered and dried to obtain the flaky chromium oxide agent.
[0089] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 5%.
[0090] A method for preparing a water-absorbing ceramic material in this embodiment comprises the following steps:
[0091] Dolomite, diatom mud, modified nano zinc oxide agent, clay, filler modifier and water are stirred and mixed, ball milled in a ball mill for 2 hours at a ball mill speed of 1000r / min, put into a mold for forming, and finally sintered to obtain a water-absorbing ceramic material.
[0092] The sintering temperature of this embodiment is 1230° C. and the sintering time is 5 hours.
[0093] The present embodiment provides an application of a water-absorbing ceramic material, wherein the water-absorbing ceramic material is applied to coasters, tea trays, photo frames, hooks, refrigerator magnets, heat-insulating pads, ceramic paintings, and the like.
[0094] Embodiment 3: A water-absorbing ceramic material, comprising the following raw materials in parts by weight:
[0095] 37.5 parts of dolomite, 17.5 parts of diatom mud, 7 parts of modified nano zinc oxide agent, 3.5 parts of clay, 5.5 parts of filler modifier, and 22.5 parts of water.
[0096] The preparation method of the modified nano zinc oxide agent of this embodiment is:
[0097] S01: First, prepare a 5% by weight dopamine Tris solution and a 4% by weight aluminum nitrate solution; then, add 2 parts by weight of silane coupling agent KH550 and 3 parts of hollow glass microspheres to 3.5 parts of the dopamine Tris solution, and then add 1.5 parts of the aluminum nitrate solution, stir well, and obtain a modified solution;
[0098] S02: Stirring and modifying the nano zinc oxide in a modification liquid of 4 times the total weight of the nano zinc oxide, and completing the stirring to obtain a nano zinc oxide liquid;
[0099] S03: 4 parts of medical stone, 3 parts of lanthanum oxide, 5.5 parts of sodium alginate solution and 3 parts of sodium silicate powder are mixed uniformly by weight, then filtered and dried, and heat treated at 220° C. for 1 h. After the treatment is completed, air-cooled to room temperature to obtain medical stone-lanthanide;
[0100] S04: The medical stone-lanthanide and nano zinc oxide solution are mixed in a mass ratio of 2:3, and the mixture is ball-milled at a speed of 1000 r / min for 1 h. After the ball-milling is completed, the mixture is filtered and dried to obtain a modified nano zinc oxide agent.
[0101] The stirring speed of the stirring modification treatment in this embodiment is 375 r / min, and the stirring is 10 min.
[0102] The mass fraction of the sodium alginate solution in this embodiment is 5%.
[0103] The preparation method of the filler modifier of this embodiment is:
[0104] S11: first prepare a 5% by mass yttrium nitrate solution and a phosphate buffer solution with a pH value of 6.0; then evenly mix the nano titanium dioxide, the yttrium nitrate solution and the phosphate buffer solution in a weight ratio of 2:5:1 to obtain a nano titanium dioxide agent;
[0105] S12: ultrasonically treat the flaky chromium oxide agent and the nano titanium dioxide agent in a weight ratio of 2:5. After the ultrasonic treatment is finished, filter and dry to obtain a filler modifier.
[0106] The ultrasonic power of the ultrasonic treatment in this embodiment is 375W, and the ultrasonic time is 25min.
[0107] The preparation method of the flaky chromium oxide agent of this embodiment is:
[0108] 4 parts of nano calcium carbonate, 1.5 parts of vermiculite and 1.5 parts of carboxymethyl cellulose were added to 6.5 parts of sodium lignin sulfonate solution by weight, and stirred sufficiently to obtain a ball mill;
[0109] The flaky chromium oxide and the ball milling agent were mixed in a weight ratio of 5:3 and ball milled at a ball milling speed of 1500 r / min for 1 hour. After the ball milling was completed, the mixture was filtered and dried to obtain the flaky chromium oxide agent.
[0110] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 3.5%.
[0111] A method for preparing a water-absorbing ceramic material in this embodiment comprises the following steps:
[0112] Dolomite, diatom mud, modified nano zinc oxide agent, clay, filler modifier and water are stirred and mixed, ball milled in a ball mill for 2 hours at a ball mill speed of 1000r / min, put into a mold for forming, and finally sintered to obtain a water-absorbing ceramic material.
[0113] The sintering temperature of this embodiment is 1220° C. and the sintering time is 5 hours.
[0114] The present embodiment provides an application of a water-absorbing ceramic material, wherein the water-absorbing ceramic material is applied to coasters, tea trays, photo frames, hooks, refrigerator magnets, heat-insulating pads, ceramic paintings, and the like.
[0115] Comparative Example 1:
[0116] The difference from Example 3 is that the modified nano zinc oxide agent is replaced by nano zinc oxide.
[0117] Comparative Example 2:
[0118] The difference from Example 3 is that the modified nano zinc oxide agent is not treated with a modified liquid, that is, steps S01 and S02 are cancelled, and the nano zinc oxide liquid in step S04 is replaced by nano zinc oxide.
[0119] Comparative Example 3:
[0120] The difference from Example 3 is that no silane coupling agent KH550 and hollow glass microspheres are added to the modified liquid.
[0121] Comparative Example 4:
[0122] The difference from Example 3 is that no aluminum nitrate solution is added to the modified solution, and the dopamine Tris solution is replaced by water.
[0123] Comparative Example 5:
[0124] The difference from Example 3 is that medical stone-lanthanide is not added in the preparation of the modified nano zinc oxide agent.
[0125] Comparative Example 6:
[0126] The difference from Example 3 is that lanthanum oxide and sodium silicate powder are not added in the preparation of medical stone-lanthanide.
[0127] Comparative Example 7:
[0128] The difference from Example 3 is that no medical stone is added in the preparation of medical stone-lanthanide, and the heat treatment at 220° C. for 1 h is not adopted.
[0129] Comparative Example 8:
[0130] The difference from Example 3 is that no filler modifier is added.
[0131] Comparative Example 9:
[0132] The difference from Example 3 is that no nano titanium dioxide agent is added to the filler modifier.
[0133] Comparative Example 10:
[0134] The difference from Example 3 is that no flake chromium oxide agent is added to the filler modifier.
[0135] Comparative Example 11:
[0136] The difference from Example 3 is that no nano calcium carbonate or vermiculite is added in the preparation of the flaky chromium oxide agent.
[0137] The water-absorbing ceramic materials of Examples 1-3 and Comparative Examples 1-11 were tested for their antibacterial and water absorption properties under normal conditions. At the same time, the water-absorbing ceramic materials were ball-milled at a rotation speed of 500 r / min for 1 hour, and tested for their antibacterial and water absorption properties under wear-resistant conditions. The performance measurement results are shown in Table 1.
[0138] Table 1 Test results of water-absorbing ceramic materials performance of Examples 1-3 and Comparative Examples 1-11:
[0139]
[0140] From Examples 1-3 and Comparative Examples 1-11, it can be concluded that the antibacterial property and water absorption rate of Escherichia coli in Example 3 of the present invention can achieve coordinated improvement, and the performance stability of the water-absorbing ceramic material under wear-resistant conditions is remarkable;
[0141] It can be seen from Comparative Example 1, Comparative Example 8 and Example 3 that the modified nano zinc oxide agent is replaced by nano zinc oxide and no filler modifier is added, and the performance of the water-absorbing ceramic material is significantly deteriorated, especially under wear-resistant conditions, the performance of the water-absorbing ceramic material is significantly deteriorated. Only by using the two in combination and synergistic effect, the performance effect of the water-absorbing ceramic material is most significant;
[0142] It can be seen from Comparative Examples 1-7 and Example 3 that the performance of the water-absorbing ceramic material has a tendency to deteriorate when the modified nano zinc oxide agent is prepared without using a modified liquid, the silane coupling agent KH550 and hollow glass microspheres are not added to the modified liquid, the aluminum nitrate solution is not added to the modified liquid, the dopamine Tris solution is replaced by water, the medical stone-lanthanide body is not added to the modified nano zinc oxide agent, the lanthanum oxide and sodium silicate powder are not added to the medical stone-lanthanide body, and the medical stone-lanthanide body is not heat-treated at 220° C. for 1 h. Only the modified nano zinc oxide agent obtained by the modified liquid obtained by the method of the present invention and the medical stone-lanthanide body has the most significant performance effect on the water-absorbing ceramic material, and the replacement by other methods is not as obvious as the effect of the present invention;
[0143] It can be seen from Comparative Examples 9-11 and Example 3 that when no nano titanium dioxide agent is added to the filler modifier, no flaky chromium oxide agent is added to the filler modifier, and no nano calcium carbonate and vermiculite are added in the preparation of the flaky chromium oxide agent, the performance of the water-absorbing ceramic material tends to deteriorate. Only when the flaky chromium oxide agent obtained by the specific method of the present invention is combined with the nano titanium dioxide agent, the performance effect of the water-absorbing ceramic material is the most significant.
[0144] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0145] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A water-absorbing ceramic material, characterized in that: It includes the following raw materials in parts by weight: 35-40 parts of dolomite, 15-20 parts of diatom mud, 6-8 parts of modified nano zinc oxide agent, 2-5 parts of clay, 4-7 parts of filler modifier, and 20-25 parts of water; The preparation method of the modified nano zinc oxide agent is: S01: First, prepare a 5% by weight dopamine Tris solution and a 4% by weight aluminum nitrate solution; then, add 1-3 parts by weight of silane coupling agent KH550 and 2-4 parts by weight of hollow glass microspheres to 2-5 parts by weight of the dopamine Tris solution, and then add 1-2 parts by weight of the aluminum nitrate solution, stir thoroughly, and obtain a modified solution; S02: Stirring and modifying the nano zinc oxide in a modification liquid 3-5 times the total weight of the nano zinc oxide, and completing the stirring to obtain a nano zinc oxide liquid; S03: 3-5 parts of medical stone, 2-4 parts of lanthanum oxide, 4-7 parts of sodium alginate solution and 2-4 parts of sodium silicate powder are mixed uniformly by weight, then filtered and dried, and heat treated at 210-230° C. for 1 hour. After the treatment is completed, air-cooled to room temperature to obtain medical stone-lanthanide; S04: mixing medical stone-lanthanide and nano zinc oxide solution in a mass ratio of 2:3, ball milling at a speed of 1000 r / min for 1 h, filtering and drying after the ball milling to obtain a modified nano zinc oxide agent; The preparation method of the filler modifier is: S11: first prepare a yttrium nitrate solution with a mass fraction of 4-6% and a phosphate buffer solution with a pH value of 6.0; then evenly mix the nano-titanium dioxide, the yttrium nitrate solution and the phosphate buffer solution in a weight ratio of 2:5:1 to obtain a nano-titanium dioxide agent; S12: ultrasonically treating the flaky chromium oxide agent and the nano titanium dioxide agent in a weight ratio of 2:5, filtering and drying after the ultrasonic treatment to obtain a filler modifier; The preparation method of the flaky chromium oxide agent is as follows: Add 3-5 parts of nano calcium carbonate, 1-2 parts of vermiculite and 1-2 parts of carboxymethyl cellulose by weight to 5-8 parts of sodium lignin sulfonate solution, stir well, and obtain a ball mill; The flaky chromium oxide and the ball milling agent were mixed in a weight ratio of 5:3 and ball milled at a ball milling speed of 1500 r / min for 1 hour. After the ball milling was completed, the mixture was filtered and dried to obtain the flaky chromium oxide agent.
2. The water-absorbing ceramic material according to claim 1, characterized in that: The stirring speed of the stirring modification treatment is 350-400 r / min, and the stirring is for 10 minutes.
3. The water-absorbing ceramic material according to claim 1, characterized in that: The mass fraction of the sodium alginate solution is 4-6%.
4. The water-absorbing ceramic material according to claim 1, characterized in that: The ultrasonic power of the ultrasonic treatment is 350-400W, and the ultrasonic time is 20-30min.
5. The water-absorbing ceramic material according to claim 1, characterized in that: The mass fraction of the sodium lignin sulfonate solution is 2-5%.
6. A method for preparing a water-absorbing ceramic material, used for preparing the water-absorbing ceramic material according to any one of claims 1 to 5, characterized in that: The following steps are involved: Dolomite, diatom mud, modified nano zinc oxide agent, clay, filler modifier and water are stirred and mixed, ball milled in a ball mill for 2 hours at a ball mill speed of 1000r / min, put into a mold for forming, and finally sintered to obtain a water-absorbing ceramic material.
7. The method for preparing a water-absorbing ceramic material according to claim 6, characterized in that: The sintering temperature is 1210-1230° C., and the sintering time is 5 hours.
8. An application of a water-absorbing ceramic material, characterized in that: The water-absorbing ceramic material as claimed in any one of claims 1 to 5 is applied to coasters, tea trays, photo frames, hooks, refrigerator magnets, heat insulation pads or ceramic paintings.
Citation Information
Patent Citations
Material having bactericidal and peculiar smell removing functions and used for automotive linings
CN106222883A
Low-temperature once-firing ceramic product and manufacturing technology thereof
CN108017369A